2011
DOI: 10.1007/s00038-010-0229-1
|View full text |Cite
|
Sign up to set email alerts
|

Extreme temperatures and mortality in the North of Spain

Abstract: The deleterious effect of increasing temperatures in summer is more pronounced than the beneficial effect of a similar increase in winter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…As for gender, our review revealed inconsistency regarding its modification effect on the association between air-pollution and weather exposure and mortality and hospital admission health outcomes. Nevertheless, most of the reviewed studies have found that females have higher risks of mortality and/or hospital admission after exposure to air-pollution and/or weather fluctuations beyond region-specific thresholds including hot and cold temperatures [9,47,57,58,65,78,[109][110][111][112]. Whereas some studies found higher risks of mortality and/or hospital admissions among males in relation to air-pollution and/or weather exposure [25,40,42,59,70,113,114].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As for gender, our review revealed inconsistency regarding its modification effect on the association between air-pollution and weather exposure and mortality and hospital admission health outcomes. Nevertheless, most of the reviewed studies have found that females have higher risks of mortality and/or hospital admission after exposure to air-pollution and/or weather fluctuations beyond region-specific thresholds including hot and cold temperatures [9,47,57,58,65,78,[109][110][111][112]. Whereas some studies found higher risks of mortality and/or hospital admissions among males in relation to air-pollution and/or weather exposure [25,40,42,59,70,113,114].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the reviewed studies stratified and adjusted their analysis by age and gender [25,40,51,[53][54][55][56][57][58][59][60][61]. Socio-economic deprivation, education attainment, income level, marital status, and occupational class were considered as confounders or effect modifiers in some of the reviewed studies [25,58,[62][63][64][65][66].…”
Section: The Adjustments and Effect Modifications For The Association Of Airpollution And Weather Exposure With Mortality And Hospital Admentioning
confidence: 99%
“…Heat-related mortality is, presumably, one of the most comprehensively studied consequences of climate change (Sera et al 2019). More frequent and longer heat waves increase mortality and morbidity, as demonstrated, for example, by Cheng et al (2014) for China and Gomez-Acebo et al (2012) for the north of Spain. Although mostly older people are affected, social and economic factors also play an important role in vulnerability to temperature extremes (Mari-Dell' Olmo et al 2019).…”
mentioning
confidence: 99%
“…But considerably more studies are related to mortality (e.g. Tobías et al 2014;Gómez-Acebo et al 2012;Maté et al 2010;Raga et al 2010;Taracido Trunk et al 2009;Borrell et al 2006;Díaz et al 2006). The seasonal behaviour of morbi-mortality, especially pronounced in respiratory pathologies, shows clear increases during the winter and minimum values in summertime (Montero et al 2010;Raga et al 2010;Analitis et al 2008;Díaz et al 2005).…”
Section: Introductionmentioning
confidence: 99%